A study on analytical solutions of one of the important shallow water wave equations and its stability analysis - Deniz, H. Arzu; Ozkan, E. Mehmet; Ozkan, Ayten (IOP Publishing Ltd, 2024)
The present research uses the modified w/ g nonlinear time fractional integro-differential Kadomtsev-Petviashvili ( KP ) hierarchy equation with beta fractional derivative. The modified w/ g analytical solutions to nonlinear equations. The suggested approach produces three sorts of solutions: trigonometric, hyperbolic, and rational. These answers have been discovered with the aid of a software tool. Additionally, stability analysis of observed governing model solutions is used to validate scientific calculations. Furthermore, the 3-dimensional, contour, and 2-dimensional images are provided for a better understanding of the behavior of the solutions.-expansion technique to give analytical solutions for the-expansion technique is an important method for fi nding
Keywords: integro differential equation; KP hierarchy equation; beta derivative; modified w/g-expansion method; stability analysis; Physics